Prediktor Marital Satistisfaction: Adakah Pengaruh Adult Attachment dan Family Resilience - Arimbi Apriliani; Ria Wardhani; Jane Savitri (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
Marital satisfaction is something which every couple would like to achieve. Adult attachment and family resilience can affect marital satisfaction. This study had the objective to determine the effect of adult attachment and family resilience on marital satisfaction with married female respondents. Then it observed in depth the relationship between the dimensions of adult attachment, family resilience and marital satisfaction. This study was conducted on 167 respondents with the characteristics of wives; in the early adulthood with the marriage age of more than five years; monogamous and in their first marriage. The measuring instrument used was Adult attachment using the Experience in Close Relationship Scale–Short Form (ECR-S), the Walsh Family Resilience Questionnaire for family resilience, and ENRICH Marital Satisfaction Scale for marital satisfaction. Each measuring instrument was tested for validity and reliability. Data processing used multiple regression test to analyze the effects and the effects were seen simultaneously and observed to see the effects partially. The results of the analysis show that all have significant effects.